Indicators of dairy cow transition risks: Metabolic profiling revisited - Van Saun, R. J. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2016)
Periparturient disease conditions affecting transition dairy cows have been recognized as a critical contributor to impaired dairy performance and have become a focal point of herd diagnostic investigations. Over the past 40 years use of blood sampling in the form of metabolic profi - ling has been applied to herd diagnostics with mixed impressions of diagnostic robustness. Research has greatly increased our understan - ding of underpinning mechanisms related to cow biology, ma nagement, environment and their interactions responsible for per ipartum diseases. Elevated β-hydroxybutyrate (BHB) concentration (> 1.2 mmol/l) within 7–10 days following calving identifies high risk cows for therapeutic intervention. Herd evaluations with 15–25% of first week fresh cows with elevated BHB indicates significant disease risk and productive losses. Elevated peripartal serum nonesterified fatty acids (NEFA) also indicate increased disease risk. This review discusses documented (BHB, NEFA) and other potential analytes using individual or pooled samples useful for disease risk assessment or nutritional status and their application in risk-based or herd screening methods of herd metabolic profiling diagnostics. A pooled sample approach modified from the original Compton Metabolic Profile allows for more economic assessment of multiple analytes, though interpretation and herd-size application may be limited. Pooled samples between 5 and 10 individuals accurately represent arithmetic means of individuals. Most importantly metabolic profiles must be used in concert with other diagnostic metrics of animal and facility evaluations, body condition scoring and ration evaluation to be fully useful in herd evaluations.
Keywords: Transition cow; metabolic profile; herd diagnostics; metabolic disease